Comparative analysis of the nutritional quality of plant-based and traditional meat products across European markets - Filip, Cristina; Kovács, Béla; Casian, Tibor; Miklos, Amalia; Pop, Paula Nistor; Istrate, Tudor-Ionuț; Hodoroga, Victoria; Tero-Vescan, Amelia (Frontiers in Nutrition, 2025)
IntroductionThe increasing global demand for plant-based meat (PBM) alternatives highlights the need for comprehensive assessments of their nutritional quality in comparison to traditional meat products.MethodsThis study evaluates the nutritional profiles of PBM and meat products from major supermarket chains in Romania, Germany, and Ireland. The analysis focused on key nutritional parameters, including energy value, macronutrient composition, and fiber content.ResultsPBM products exhibited a lower energy density, reduced saturated fat content, and significantly higher fiber levels than their meat counterparts. However, protein content remained lower in PBM products, while salt levels varied by category. Notably, products from Romania displayed inferior nutritional profiles compared to those from Germany and Ireland, with higher energy, fat, and salt content but lower fiber levels.ConclusionThese findings underscore the need for policy-driven improvements in PBM formulations and standardized nutritional guidelines across markets. The study contributes to the growing body of research on sustainable dietary transitions and their implications for public health.